Influence of tire dynamics on a braking process with ABS. - Pérez-Fernández, Javier; Alcázar-Vargas, Manuel Gonzalo; Velasco García, Juan María; Cabrera-Carrillo, Juan Antonio; Castillo-Aguilar, Juan Jesús (Elsevier, 2021)
This article analyzes the influence of the proper modeling of the anti-lock brake system control loop components. Both the use of a stationary tire model and not considering the delays due to measurement, estimation, and actuation tend to be overlooked. Therefore, this affects the efficiency of the control algorithms developed through simulation. Thus, this work proposes to analyze the influence of the modeling of the components by performing experimental tests on a flat-track test bench. These tests demonstrate the need for taking these effects into account
Keywords: Vehículos - Resistencia a las colisiones; Tire; Modeling; Testing; Validation; Active safety systems